(untitled) (Advances in Knowledge Representation, 2022)
In a world where evolution is continuous, knowledge management and information management are recognized as important strategic pillars in business performance. In view of this scenario, the objective of this article was to verify the existence of works that proposed how to carry out the integration of knowledge management, objectives and key results and organizational performance. Therefore, the research was carried out on a qualitative and exploratory basis through a systematic review of the literature, since it is an adequate method for this purpose, as it guarantees reproducibility, reliability and explicit research methods. As a result, it was possible to observe the scarcity of publications related to knowledge management with the integration of organizational performance and few researches associating objectives and key results, however an influence of information sharing practices was identified as a potential for the adoption of objectives and key results for improving organizational performance. Knowledge management contributes to improving organizational performance through the mediation and/or influence of other variables, such as social/human capital, organizational learning, knowledge mutation, organizational leadership, organizational trust, organizational creativity, decision-making style, business process features of innovation and entrepreneurial orientation.